Topical Iodine-Induced Thyrotoxicosis in a Newborn with a Giant Omphalocele - Sonali Malhotra; Shilpa Kumta; Alok Bhutada; Elka Jacobson-Dickman; Roja Motaghedi (Thieme Medical Publishers, Inc., 2016)
Abstract Introduction Neonatal thyrotoxicosis is a life-threatening condition with potentially irreversible neurologic sequelae. Most cases are seen in neonates born to mothers with Graves' disease. Topical iodine-induced hypothyroidism has been reported in neonates, but iodine-induced neonatal hyperthyroidism has not been described; albeit a familiar entity in adults. Case Description Herein we present a unique case of a neonate, born with a giant omphalocele, who was treated with topical povidone-iodine dressings to promote escharification, in preparation for delayed surgical closure. By third day of life (DOL), the baby presented with a suppressed thyroid stimulating hormone of 0.59 µIU/mL, elevated free thyroxine of 5.63 ng/dL, and frank cardiovascular manifestations of thyrotoxicosis. After replacement of the topical iodine dressings with iodine-free silver sulfadiazine, the thyroid status gradually improved with complete resolution of hyperthyroidism by 17th DOL. Conclusion This case emphasizes that significant topical iodine exposure can result in both hypothyroidism and hyperthyroidism, and therefore, vigilance in monitoring thyroid function is imperative.